How do Learning Support Centres support us? : student voices from a secondary school : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Educational Psychology at Massey University, Manawatu, New Zealand - Jacobs, Ria (Massey University, 2018)
The Committee on the Rights of the Child has identified article 12 as one of the four general principles of United Nations Convention on the Rights of the Child (UNCRC), and the right under Article 12 of all children to be heard and taken seriously as one of the fundamental values of the Convention. Since the adoption of the Convention in 1989, considerable progress has been made at national and global levels in the development of legislation, policies and methodologies to promote the implementation of Article 12 in educational systems. However, the implementation of the child’s right to express their view on a wide range of issues that affect them continues to be impeded by many long-standing practices, attitudes, political and economic barriers in most societies. This qualitative research project was aimed at the perceptions and experiences of six secondary school students ranging from year 9 – year 13 at a multicultural school in New Zealand who received support at a Learning Support Centre (LSC). The methodology centred on exploring the perspectives and attitudes of the students who attended the LSC and whether they had the opportunity to express their views in regards to their learning in the LSC as specified in Article 12 of UNCRC. Semi-structured interviews focused on the students’ assessment of their learning in the LSC and compared the learning assistance in the LSC to the support they received in their regular classroom. The interview results indicated that students were very supportive and appreciative of the values that the school was promoting and they felt proud to be students of the school. They appreciated the support and encouragement received in the LSC which helped them to learn in regular classes and enhanced their confidence to achieve. Students made progress in their reading and comprehension of subject information in their regular subjects as well applying the skills learnt in the LSC to other areas. However, the results also indicated that students were not always able to express their views on issues that affected their learning. Students did not always have the right to make decisions. At times students’ decisions were less likely to be considered than those of parents and teachers, and the curriculum could also impose restrictions on students’ autonomy.
Keywords: Motivation in education -- New Zealand; Help-seeking behavior -- New Zealand; Student-centered learning -- New Zealand; High school students -- New Zealand -- Attitudes; Children's rights -- New Zealand; Convention on the Rights of the Child|d(1989)